2013
DOI: 10.1155/2013/901821
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Transduction of Endometrial Decidual Tissue Multipotent Mesenchymal Stromal/Stem Cells from Menstrual Blood

Abstract: Mesenchymal stromal/stem cells (MSCs) reveal progenitor cells-like features including proliferation and differentiation capacities. One of the most historically recognized sources of MSC has been the bone marrow, while other sources recently include adipose tissue, teeth, bone, muscle, placenta, liver, pancreas, umbilical cord, and cord blood. Frequently, progenitor isolation requires traumatic procedures that are poorly feasible and associated with patient discomfort. In the attempt to identify a more approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 41 publications
(54 reference statements)
6
63
0
7
Order By: Relevance
“…These findings are in agreement with some previous studies (Da Sacco et al, 2010;Semenov et al, 2010;Abumaree et al, 2013;Rossignoli et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in agreement with some previous studies (Da Sacco et al, 2010;Semenov et al, 2010;Abumaree et al, 2013;Rossignoli et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
“…Conversely, the antigen profiles were negative (Ͻ2%) for the hematopoietic markers CD34 (0.7 Ϯ 0.1% of positive cells) and CD45 (1.5 Ϯ 0.4% of positive cells), as required for MSCs (20). In addition, the cells expressed CD56 (95.9 Ϯ 3.5% of positive cells), which is considered a natural killer and neuronal and muscle marker but has also been described as a marker of subsets of MSCs derived from human bone marrow (4,8) and menstrual blood (51).…”
Section: Resultsmentioning
confidence: 99%
“…Menstrual blood-derived stem cells (MenSCs) are novel stem cells with the basic characteristics of MSCs, but expressing different molecular markers. Meng et al found that MenSCs expressed OCT-4, but not NANOG or SSEA-4 [5][6][7] , while Rossignoli et al [8] reported that 19.4% of MenSCs were SSEA-4-positive by flow cytometry. Zemel'ko et al [9] showed high expression of SSEA-4 by immunofluorescence.…”
Section: Introductionmentioning
confidence: 99%